Prevalence and factors related to dental caries among pre-school children of Saddar town, Karachi, Pakistan: a cross-sectional study - Dawani Narendar; Nisar Nighat; Khan Nazeer; Syed Shahbano; Tanweer Navara (BMC, 2012)
Abstract Background Dental caries is highly prevalent and a significant public health problem among children throughout the world. Epidemiological data regarding prevalence of dental caries amongst Pakistani pre-school children is very limited. The objective of this study is to determine the frequency of dental caries among pre-school children of Saddar Town, Karachi, Pakistan and the factors related to caries. Methods A cross-sectional study of 1000 preschool children was conducted in Saddar town, Karachi. Two-stage cluster sampling was used to select the sample. At first stage, eight clusters were selected randomly from total 11 clusters. In second stage, from the eight selected clusters, preschools were identified and children between 3- to 6-years age group were assessed for dental caries. Results Caries prevalence was 51% with a mean dmft score being 2.08 (±2.97) of which decayed teeth constituted 1.95. The mean dmft of males was 2.3 (±3.08) and of females was 1.90 (±2.90). The mean dmft of 3, 4, 5 and 6- year olds was 1.65, 2.11, 2.16 and 3.11 respectively. A significant association was found between dental caries and following variables: age group of 4-years (p-value ² 0.029, RR = 1.248, 95% Bias corrected CI 0.029-0.437) and 5-years (p-value ² 0.009, RR = 1.545, 95% Bias corrected CI 0.047-0.739), presence of dental plaque (p-value ² 0.003, RR = 0.744, 95% Bias corrected CI (−0.433)-(−0.169)), poor oral hygiene (p-value ² 0.000, RR = 0.661, 95% Bias corrected CI (−0.532)-(−0.284)), as well as consumption of non-sweetened milk (p-value ² 0.049, RR = 1.232, 95% Bias corrected CI 0.061-0.367). Conclusion Half of the preschoolers had dental caries coupled with a high prevalence of unmet dental treatment needs. Association between caries experience and age of child, consumption of non-sweetened milk, dental plaque and poor oral hygiene had been established.